Synthesis and physical-chemical properties of 3-benzyl-8-propylxanthine and its water-soluble salts - E. K. Mikhal’chenko; K. V. Аleksandrova; S. V. Levich (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
Aim. Selection of basic compounds is a key moment of the novel drug substances development process. Nowadays, it is possible to model the properties of biologically active substances with the help of computer technologies and the special software. We selected 3-benzyl-8-propylxanthine as a promising basic compound with a large variability of further chemical modification by insertion of well-known pharmacophores. Our decision was based on in silico-calculations.